Enhanced production of high-value polyunsaturated fatty acids (PUFAs) from potential thraustochytrid Aurantiochytrium sp. (February 2023) - Chauhan, Ajeet Singh; Patel, Anil Kumar; Chen, Chiu-Wen; Chang, Jo-Shu; Michaud, Philippe; Dong, Cheng-Di; Singhania, Reeta Rani
Graphical abstract: Highlights: Aurantiochytrium sp. was identified as high ω-3 PUFAs and low ω-6 producer . A 30 g/L glucose was determined as the best optimized concentration. The maximum yield of lipid and DHA at 30 g/L glucose were 4.30 and 1.34 g/L. Lipid and DHA content was 62.4 and 33.49 % of total biomass and total lipid. Relative PUFA was maximum 46.97 % (DHA) at 10 g/L glucose concentration. Abstract: Due to growing health concerns, the urban population is utterly inclined towards a healthy lifestyle and incorporated nutritional food supplements to lower common health risks. The ω-3 and ω-6 PUFAs consumption is increasing, hence alternative commercial production is essentially developed. The microbial source is an emerging platform to overcome the global demand for omega PUFAs. Marine oleaginous protist Aurantiochytrium sp. found a potential source to produce substantial DHA and SFA. The objective of the present research was to enhance the PUFA yield by optimizing maximum tolerable glucose concentration with a suitable nitrogen ratio (10:1). The maximum lipid and DHA yield and content were determined 4.30, 1.34 g/L, and 62.4, 33.49 % of total biomass and lipid at 30 g/L glucose respectively, which is one of among highest reported, however relative PUFA was maximum 46.97 % (DHA) in total lipid at 10 g/L glucose. Remaining 42–53.6 % SFA could be used for biodiesel.